The Effect of Service Leadership and Coworker Support on Employee Retention at Ulunoyo Community Health Center South Nias Regency - Buulolo, Sanida; Waruwu, Eliyunus; Gulo, Heniwati; Buulolo, Nanny Artatina; Halawa, Forman (ProBisnis : Jurnal Manajemen, 2025)
This study investigates the influence of service leadership and coworker support on employee retention at Ulunoyo Community Health Center, South Nias Regency. High employee turnover in the past three years has disrupted health service continuity and effectiveness. Service-oriented leadership and coworker support are assumed to be significant factors influencing retention in public health institutions. A quantitative approach was employed using a saturated sampling technique involving all 44 employees of Puskesmas Ulunoyo. Data were collected through questionnaires measured by a Likert scale, which had been tested for validity and reliability. Analysis was conducted using classical assumption tests and multiple linear regression with SPSS software. The findings reveal that service leadership positively and significantly affects employee retention, coworker support positively and significantly influences retention, and both variables simultaneously contribute significantly to employee retention. These results suggest that effective human resource management through service leadership and supportive coworker relationships enhances employee loyalty and reduces turnover intention. The study highlights the importance of strengthening service-based leadership practices and fostering coworker support to improve organizational sustainability. For healthcare institutions, this research provides valuable insights into designing strategies that not only enhance retention but also improve overall service quality for the community.